Jonathan M. Schwartz, Pieces of Mosaic: an essay on the Making of Macedonia, Tabahon, Skopje 2010, ISBN 978-608-4566-02-1 (ЕтноАнтропоЗум, 2011)
In 2010 in the production of the publishing house TABAHON from Skopje the book Pieces of Mosaic: an essay on the Making of Macedonia was released. It is a piece from an American anthropologist who lives and works in Denmark, Jonathan Matthew Schwartz.